2017
DOI: 10.1002/ptr.5831
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhetinic Acid Accelerates the Clearance of Triptolide through P‐gp In Vitro

Abstract: Triptolide (TP) is an active ingredient isolated from Tripterygium wilfordii Hook. f. (TWHF), which is a traditional herbal medicine widely used for the treatment of rheumatoid arthritis and autoimmune disease in the clinic. However, its adverse reactions of hepatotoxicity and nephrotoxicity have been frequently reported which limited its clinical application. The aim of this study was to investigate the mechanism of glycyrrhetinic acid (GA) effecting on the elimination of TP in HK-2 cells and the role of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Based on the data from the included studies, 0.5 to 1.5 mg·kg −1 ·day −1 of TwHF is recommended in future clinic application with less toxicity. Some researches also had attempted the following approaches to decrease its toxicity: (a) modify structure of its bioactive substances; (b) combine compounds reasonably; (c) purify its extracts; (d) optimize its extraction methods; and (e) change its formulations and administration methods (Hewitson, Ignatova, Ye, Chen, & Sutherland, 2009;Li et al, 2017;Nan, Zheng, & Xu, 2015;Shao et al, 2006;Tang & Zuo, 2012;Yuan et al, 2015;Zhang et al, 2014a;Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data from the included studies, 0.5 to 1.5 mg·kg −1 ·day −1 of TwHF is recommended in future clinic application with less toxicity. Some researches also had attempted the following approaches to decrease its toxicity: (a) modify structure of its bioactive substances; (b) combine compounds reasonably; (c) purify its extracts; (d) optimize its extraction methods; and (e) change its formulations and administration methods (Hewitson, Ignatova, Ye, Chen, & Sutherland, 2009;Li et al, 2017;Nan, Zheng, & Xu, 2015;Shao et al, 2006;Tang & Zuo, 2012;Yuan et al, 2015;Zhang et al, 2014a;Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, TW has gastrointestinal reactions, liver damage, menstrual disorders, reproductive problems, adverse skin reactions, hematological events, cardiovascular events and nephrotoxicity ( Zhang C. et al, 2016 ; Brown, 2017 ). Therefore, researchers should devote themselves to finding bioactive substances with safe doses and modifying their structures; reasonable combination of drugs; purifying their extracts; optimizing extraction methods; changing their dosage forms and administration methods, reduce the toxicity, so as to make TW better serve the clinic ( Shao et al, 2006 ; Hewitson et al, 2009 ; Tang and Zuo, 2012 ; Zhang et al, 2014 ; Yuan et al, 2015 ; Zhang B. et al, 2016 ; Li Z. et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This signified that DDIs might occur when TP and transporter-related substrate drugs were simultaneously administered, which may aggravate or reduce liver damage. For instance, a study on TP combined with glycyrrhetinic acid to reduce its toxicity was reported (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%